2016
DOI: 10.1007/s12519-016-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

Allergen specific sublingual immunotherapy in children with asthma and allergic rhinitis

Abstract: At least 3 years of treatment and stable asthma before the immunotherapy are positive predictors of good clinical efficacy and tolerability of SLIT. SLIT reduces the symptoms of allergic diseases and the use of medicaments, and improves the quality of life of children with the diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
0
15
0
2
Order By: Relevance
“…A recent review summarized over 80 randomized double-blind placebo-controlled trials, and several reviews of both adult and children populations and concluded that, in most studies, the overall occurrence of systemic side effects is similar between placebo and active groups (7). To date, only few cases of anaphylaxis have been reported with SLIT (38), and some of these are probably due to overdose (72). …”
Section: Safetymentioning
confidence: 99%
“…A recent review summarized over 80 randomized double-blind placebo-controlled trials, and several reviews of both adult and children populations and concluded that, in most studies, the overall occurrence of systemic side effects is similar between placebo and active groups (7). To date, only few cases of anaphylaxis have been reported with SLIT (38), and some of these are probably due to overdose (72). …”
Section: Safetymentioning
confidence: 99%
“…High level of anxiety as well as higher incidence of depression and other physiological disorders can be seen in children and adolescents with asthma, allergic rhinitis and atopic dermatitis. A certain number of studies confirmed the impact of SLIT on all previous mentioned aspects of quality of life [76,77].…”
Section: Clinical Efficacy Of Slit Still Matter Of a Debatementioning
confidence: 74%
“…They are easily contained by transitorily diminishing the dose or antihistamine premedication for several weeks. Systemic reactions and asthma exacerbations are not common [ 79 ], while anaphylaxis has been reported anecdotally [ 85 , 86 ], and no fatality has been registered. A very low percentage of patients discontinues SLIT because of side effects [ 20 , 39 , 85 ].…”
Section: Safetymentioning
confidence: 99%